Effectiveness of Teacher-Made Supplemental Learning Resource Material in Mathematics for Diverse Learners - Analyn D Ramos (ASEAN Multidisciplinary Research Journal, 2022)
Development of mathematics skills is one of the core targets of high-quality mathematics education. How to effectively promote mathematical skills is the focus of mathematics teaching. Relative to this, a study on the effectiveness of teacher-made supplemental learning resource material in mathematics for diverse learners was conducted. It focused on the following: development of a supplemental learning resource material in Mathematics based from the least mastered learning competencies; evaluation of jurors of the developed material; determine the effectiveness of the developed material in improving mathematics competence of three level ability groups along the strands number and number and number sense, measurement and algebra; and modifications integrated to the developed material based from the findings of the study.The developmental-evaluative-experimental method of research was used. Two types of instruments were utilized in the study: the teacher-made pretest/posttest and evaluation rating sheet. Results of the pretest gave rise to the development of a supplemental learning resource material in Mathematics for diverse learners. It was titled: “Mathematics for Diversity” which covered the following least mastered learning competencies in Grade 7 Mathematics: “writing very large or very small numbers in scientific notation”, determining the significant digits in a given situation”, “solving problems involving utilities usage”, and “evaluating algebraic expression for given values of the variables”. Furthermore, it was found out that the use of the developed material had significant effect in improving the learning competence of Grade 7 students; hence, very effective in improving the learning competence of the students.